Phosphatidylinositol biosynthesis in Saccharomyces cerevisiae: purification and properties of microsome-associated phosphatidylinositol synthase. - Fischl, A S (1983)
The membrane-associated phospholipid biosynthetic enzyme phosphatidylinositol synthase (cytidine 5'-diphospho-1,2-diacyl-sn-glycerol:myo-inositol 3-phosphatidyltransferase, EC 2.7.8.11) was purified 1,000-fold from the microsomal fraction of Saccharomyces cerevisiae. The purification procedure included Triton X-100 solubilization of the microsomal membranes, CDPdiacylglycerol-Sepharose (Larson et al., Biochemistry 15:974-979, 1976) affinity chromatography, and chromatofocusing. The procedure resulted in the isolation of a nearly homogeneous protein preparation with an apparent minimum subunit molecular weight of 34,000, as determined by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate. Phosphatidylinositol synthase was dependent on manganese and Triton X-100 for maximum activity. The pH optimum was 8.0. Thioreactive agents inhibited enzyme activity. The energy of activation was found to be 35 kcal/mol (146,540 J/mol). The enzyme was reasonably stable at temperatures of up to 60 degrees C.